Hopkins Syndrome with Mycoplasma Infection - J Gordon Millichap (Pediatric Neurology Briefs)
A 3-year-old boy with acute flaccid paralysis of the right lower limb developing one week after treatment and recovery from an acute asthma attack is reported from the Department of Child Health, Milton Keynes General Hospital, UK.